Findigkeit in unsicheren Zeiten - Solga, Heike; Huschka, Denis; Wagner, Gert G.; Eilsberger, Patricia (Ergebnisse des Expertisenwettbewerbs "Arts and Figures - GeisteswissenschaftlerInnen im Beruf", 2008)
The book deals with the situation of humanities scholars in the labour market. The starting point of the seven empirical contributions is the discrimination of humanities scholars in comparison to other university graduates. This is reflected in an above-average unemployment rate, a significantly higher prevalence of precarious employments and often a comparatively low income. The aim of the book is to determine current options and future opportunities for this occupational group on the basis of a broad empirical survey of the humanities.